2015
DOI: 10.1007/s00122-015-2472-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping of a major QTL controlling angular leaf spot resistance in common bean (Phaseolus vulgaris L.)

Abstract: Key messageA major QTL for angular leaf spot resistance in the common bean accession G5686 was fine-mapped to a region containing 36 candidate genes. Markers have been developed for marker-assisted selection.AbstractCommon bean (Phaseolus vulgaris L.) is an important grain legume and an essential protein source for human nutrition in developing countries. Angular leaf spot (ALS) caused by the pathogen Pseudocercospora griseola (Sacc.) Crous and U. Braun is responsible for severe yield losses of up to 80 %. Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 87 publications
2
75
0
4
Order By: Relevance
“…Variety G5686, also a documented source of resistance (Mahuku et al, 2009) on Pv10, identified in both G5686 (Keller et al, 2015) and CAL143 (Oblessuc et al (2012(Oblessuc et al ( , 2013 were officially named as Phg-4 and Phg-5 (Souza et al, 2015;).…”
Section: Discussionmentioning
confidence: 99%
“…Variety G5686, also a documented source of resistance (Mahuku et al, 2009) on Pv10, identified in both G5686 (Keller et al, 2015) and CAL143 (Oblessuc et al (2012(Oblessuc et al ( , 2013 were officially named as Phg-4 and Phg-5 (Souza et al, 2015;).…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases, after MAS the effect of a QTL was reduced or nullified. Subsequently, an increasing number of fine mapping studies of major-effect resistance QTL have been recently described (Keller et al 2015). For example, Ahmadi et al (2001) reported that MAS was particularly useful for validating epistatic effects between two QTL for resistance to rice yellow mottle virus, in introgression lines carrying both QTL compared to lines hosting only one of the two QTL which displayed no effects.…”
Section: Introductionmentioning
confidence: 99%
“…The PhaseolusGenes marker database has become an essential tool for cataloging bean marker diversity so that the breeding community can utilize marker information from multiple sources to facilitate MAS (Gonçalves-Vidigal et al, 2011Reinprecht et al, 2013;Oblessuc et al, 2013Oblessuc et al, , 2015Aranda et al, 2014;Keller et al, 2015;Sousa et al, 2015;Coimbra-Gonçalves et al, 2016;Perseguini et al, 2016). Because genomic resequencing of breeding parents is today a more routine practice with the lowered cost of sequencing, the PhaseolusGenes database should evolve from a marker database into a sequence database, which includes not only the current markers but also the increasingly large number (> 2,000) of genotypes that have been sequenced, including the 16 parental genotypes of the ABC projects (T. Miller and P. Gepts, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Seven QTLs on five chromosomes were identified in a IAC-UNA × CAL 143 recombinant inbred population and named ALS2.1, ALS3.1, ALS4.1, ALS4.2, ALS5.1, ALS5.2 and ALS10.1 (Oblessuc et al, 2012(Oblessuc et al, , 2013(Oblessuc et al, , 2015. Additionally, three major R genes identified in Andean G5686 (Phg G5686A , Phg G5686B and Phg G5686C ) (Mahuku et al, 2009) were later treated as quantitative loci by Keller et al (2015) and mapped to the same loci as ALS4.1, ALS4.2 and ALS9.1 (Oblessuc et al, 2012;Keller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%